Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1115/1.4006111
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Surface Effect on Heat Transfer Performance in an Oscillating Heat Pipe

Abstract: An experimental investigation of an oscillating heat pipe (OHP) with a superhydrophobic inner surface coated with a superhydrophobic self-assembled monolayer (SAM) of n-octadecyl mercaptan was conducted. The experimental results show that the oscillating motion in an OHP with a superhydrophobic surface can be generated and the OHP can function well. This is very different from the conventional wicked heat pipe, which cannot function if the inner surface is hydrophobic. The functionality of a superhydrophobic O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…frequency domain which has been generally emloyed for signal processing in hydrualic machinery (e.g., hydraulic turbines [35][36][37], pumps [38] and propellers [39,40]), will provide further inside for the analysis. For further enhancement of OHP, employment of hydrophobic surface is currently being intensively explored [41][42][43] due to the distinguishable characteristics of bubble dynamics on the surface [44]. …”
Section: Discussionmentioning
confidence: 99%
“…frequency domain which has been generally emloyed for signal processing in hydrualic machinery (e.g., hydraulic turbines [35][36][37], pumps [38] and propellers [39,40]), will provide further inside for the analysis. For further enhancement of OHP, employment of hydrophobic surface is currently being intensively explored [41][42][43] due to the distinguishable characteristics of bubble dynamics on the surface [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that the thermal resistance o f the OHP with the superhydrophobic surface was higher than that with the hydrophilic surface [16]. 11-13.…”
Section: S U P E R H Y D R O P H O B Ic S U R Fa C E O N (A ) H E a Tmentioning
confidence: 95%
“…The flow pattern and slug motion is affected by the surface wettability and the heat transfer performance of OHP depends on the oscillating motion of the slugs. Ji et al [16] studied the heat transfer performance of OHPs with superhydrophobic surface and found that the thermal resistance of the superhydrophobic surface OHP was higher than that with the hydrophilic inner sur face. Khandekar et al [15] found the surface having negligible dynamic contact angle hyster esis should be preferred in the OHPs in order to reduce the capil lary resistance under slug flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, different researchers showed that the surface wettability influences the vapor and liquid slug motion and so, the thermal performance of PHP [9] [10] [11]. Actually, the presence of thin films over internal surfaces, surrounding the vapor plugs, is related to the surface wettability.…”
Section: Introductionmentioning
confidence: 99%